Gastric Outlet Obstruction in the Current Era–A Pictorial Review on Computed Tomography Imaging - Rastogi, Ashita; Singh, Somesh; Yadav, Rajanikant (Journal of Gastrointestinal and Abdominal Radiology, 2021)
Gastric outlet obstruction is a pathophysiological entity characterized by mechanical impediment of gastric emptying, which may occur due to a variety of intrinsic or extrinsic causes affecting the antrum or pylorus or duodenum. The obstruction may be benign or malignant or secondary to a motility disorder. Imaging in gastric outlet obstruction identifies majority of these causes and may indirectly even point toward motility disorders. The advent of computed tomography imaging and its subsequent advances have allowed it to become the mainstay of evaluation of stomach, particularly in gastric outlet obstruction. In this pictorial review, a few causes of gastric outlet obstruction are exhibited.
Keywords: CT imaging; CT stomach; gastric emergencies; gastric outlet obstruction